2016
DOI: 10.1007/s11033-016-3997-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gonadal soma-derived factor involvement in Monopterus albus (protogynous rice field eel) sex change

Abstract: We studied molecular events and potential mechanisms underlying the process of female-to-male sex transformation in the rice field eel (Monopterus albus), a protogynous hermaphrodite fish in which the gonad is initially a female ovary and transforms into male testes. We cloned and identified a novel gonadal soma derived factor (GSDF), which encodes a member of the transforming growth factor-beta superfamily. gsdf expression was measured in gonads of female, intersex and male with reverse transcription-PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Although we do not know the function of Gsdf in salmon testis, it is likely that this protein has one or more roles as described in other fish species. One possible role may be associated with testis maturation, since we observed that gsdf expression was higher in immature compared to mature testis, similar to what has been observed in medaka, Japanese flounder, wrasse (Halichoeres trimaculatus) and rice field eel (Monopterus albus) [43,48,54,55]. The fact that we detected a 3.5fold lower number of gsdf reads in testis tissue devoid of germ cells compared to intact testis tissue may suggest a role for gsdf in the communication between germ cells and testicular somatic cells in Atlantic salmon.…”
Section: Gsdfsupporting
confidence: 86%
“…Although we do not know the function of Gsdf in salmon testis, it is likely that this protein has one or more roles as described in other fish species. One possible role may be associated with testis maturation, since we observed that gsdf expression was higher in immature compared to mature testis, similar to what has been observed in medaka, Japanese flounder, wrasse (Halichoeres trimaculatus) and rice field eel (Monopterus albus) [43,48,54,55]. The fact that we detected a 3.5fold lower number of gsdf reads in testis tissue devoid of germ cells compared to intact testis tissue may suggest a role for gsdf in the communication between germ cells and testicular somatic cells in Atlantic salmon.…”
Section: Gsdfsupporting
confidence: 86%
“…In O. luzonensis and sablefish, sex‐specific gsdf variants are present in genetic males and females (Myosho et al, ; Rondeau et al, ), and in Nile tilapia, chromosomally XX fish that are homozygous gsdf mutants reverse their sex to develop as males (Jiang et al, ). In addition, in two fish (three‐spot wrasse and rice field eel) that are sequential protogynous hermaphrodites, gsdf expression is up‐regulated as ovaries transform to testes (Horiguchi et al, ; Zhu et al, ). Although gsdf is not the primary genetic sex determinant in O. latipes (Japanese medaka), forced expression of gsdf on an autosome causes XX females to become males (Zhang et al, ) and gsdf knockout causes XY O. latipes to become phenotypic females, demonstrating that gsdf is strongly male determining in this species (Imai et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dmrt1 is generally considered to take charge of testicular differentiation cascade and could down-regulate cyp19a1a in vertebrates (Guiguen, Fostier, Piferrer, & Chang, 2010). Zhu, Wang, Chen, and Guan (2016) found that dmrt1 was absent in the ovary but present in Sertoli and gonia cells in testis and ovotestis of Monopterus albus, implying that it may be a essential regulatory factor for the transition of ovary to testis. The preliminary effects of sf-1, dax1 and amh on sex-inversion regulation have been demonstrated as well.…”
Section: Reproduction-related Genesmentioning
confidence: 99%